Distribution of lymph node metastasis and the extent of lymph node dissection in descending colon cancer patients. Issue 9 (26th August 2019) - Lee, Soo Young; Yeom, Seung‐Seop; Kim, Chang Hyun; Kim, Young Jin; Kim, Hyeong Rok
Abstract: Background: The optimal extent of lymph node dissection in patients with descending colon cancer is still debatable. We designed this study to evaluate the distribution of lymph node metastasis and the appropriate extent of lymph node dissection in descending colon cancer patients. Methods: We retrospectively reviewed the medical records of 118 descending colon cancer patients without distant metastasis, who underwent curative resection between January 2004 and December 2014. The distribution of lymph node metastasis was evaluated, and prognostic factors were analysed. Results: The median follow‐up period was 52 months (range 1–125 months). Twenty‐six (22.0%) patients underwent high ligation of the inferior mesenteric artery (IMA), whereas 92 (78.0%) patients underwent ligation of the left colic artery, saving the IMA. Lymph nodes at the origin of the IMA showed no metastasis in any of the 26 patients who underwent high ligation of the IMA. After propensity score matching, 3‐year disease‐free survival (80.4% versus 92.9%, P = 0.471) and 5‐year overall survival (81.8% versus 90.9%, P = 0.875) were not significantly different according to the type of IMA ligation. Conclusion: In patients with descending colon cancer, there was no lymph node metastasis at the origin of the IMA, and ligation of the IMA showed no prognostic benefit. Abstract : The optimal extent of lymph node dissection in patients with descending colon cancer is still debatable. This retrospective study evaluated lymph node metastasis of 118 descending colon cancer patients. Lymph nodes at the origin of the inferior mesenteric artery (IMA) showed no metastasis in any of the 26 patients who underwent high ligation of the IMA, and ligation of the IMA showed no prognostic benefit after propensity score matching.